THE IMPACT OF COOPERATIVE LEARNING ON THE COMMUNICATION SKILLS OF STUDENTS - B.Arzieva (Research Focus International Scientific Journal, 2025)
Cooperative learning is a way of teaching where students work together to achieve shared goals. This thesis looks at how cooperative learning affects students' communication skills, especially in terms of encouraging verbal and non-verbal communication, active listening, and interacting with others. The research shows different cooperative learning techniques and how they impact student engagement, confidence, and the ability to express ideas clearly. The results suggest that cooperative learning improves communication skills by creating interactive learning environments that encourage dialogue, problem-solving, and teamwork.